2020
DOI: 10.1002/cne.24929
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of precuneus layer III cathepsin D‐immunopositive pyramidal neurons in mild cognitive impairment and Alzheimer's disease: Evidence for neuronal signaling vulnerability

Abstract: The precuneus (PreC; Brodmann area 7), a key hub within the default mode network (DMN) displays amyloid and tau‐containing neurofibrillary tangle (NFT) pathology during the onset of Alzheimer's disease (AD). PreC layer III projection neurons contain lysosomal hydrolase cathepsin D (CatD), a marker of neurons vulnerable to NFT pathology. Here we applied single population laser capture microdissection coupled with custom‐designed microarray profiling to determine the genetic signature of PreC CatD‐positive‐layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 105 publications
0
9
0
Order By: Relevance
“…The present study indicates that telomere length alterations within hubs of the DMN are nuanced when examined in the context of AD neuropathology and cognitive performance. Future studies will evaluate telomere alterations using Q‐FISH, single‐cell and global gene expression profiling to identify the genetic signatures of cell populations that demonstrate telomere attrition in the DMN during the progression of AD 3,4 . The present findings indicate that telomeric homeostasis is affected in the PreC during the prodromal stage of AD.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The present study indicates that telomere length alterations within hubs of the DMN are nuanced when examined in the context of AD neuropathology and cognitive performance. Future studies will evaluate telomere alterations using Q‐FISH, single‐cell and global gene expression profiling to identify the genetic signatures of cell populations that demonstrate telomere attrition in the DMN during the progression of AD 3,4 . The present findings indicate that telomeric homeostasis is affected in the PreC during the prodromal stage of AD.…”
Section: Discussionmentioning
confidence: 68%
“…TRF2 interacts with lamin A/C at the nuclear lamina, 91,92 suggesting that a molecular interaction between TRF2 and the nucleoskeleton affects genomic integrity, telomere stability and chromosome structure 92 . Perhaps telosome alterations affect the AD transcriptome via DDR activation by disrupting molecular interactions with TRF2, which could play a role in the selective vulnerability of the PreC to hypometabolism, 9,10,93 energy deficits 2,5 and dysregulation of gene transcription in MCI and AD 4 . Future qualitative and quantitative immunohistochemistry will be used to investigate cellular shelterin phenotypes, telomere functionality and their correlation with the findings observed in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pyramidal cells in layer III of the dlPFC have been an important focus of research, as these neurons are critical for higher cognitive functions 30,31 , and are selectively vulnerable to tau pathology and neurodegeneration in AD 32,33 , thus providing important clues about AD etiology. Studies of these neurons in rhesus monkeys have shown that they express the molecular machinery to magnify calcium signaling in dendritic spines at glutamate synapses (Fig.…”
Section: Calcium Dysregulation As An Early Pathological Event In Admentioning
confidence: 99%
“…Several studies have earlier examined the expression of neuroinflammatory genes in the prefrontal or entorhinal cortex of the patients with AD using single nucleus transcriptome analysis [ 18 20 ]. However, there are only a few transcriptomic studies focusing on the precuneus [ 21 , 22 ], the region of the brain, where Aβ accumulation is observed in preclinical AD patients [ 23 , 24 ]. Therefore, the transcriptomic analysis of precuneus is of particular interest, as it can provide novel insights into the response of microglia to Aβ in early AD.…”
Section: Introductionmentioning
confidence: 99%